2017
DOI: 10.18203/2349-3933.ijam20172132
|View full text |Cite
|
Sign up to set email alerts
|

To study hematological profile in malaria patients

Abstract: Background: Malaria has been a problem in India for centuries and it is responsible for many deaths in rural areas. This study was done to observe hematological profile in malaria patients and to study the incidence of complications in different species of malaria patients and to find any relation with hematological changes.Methods: The study was conducted at MLN Medical College, Allahabad in the Department of Medicine between January 2016 to December 2016. One hundred consecutive patients aged 18 years or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
0
1
Order By: Relevance
“…In studies like Yadav RK et al, and Surve KM et al, had similar rates of male: female ratio which is 1.32:1 in both. 7,8 In other studies like Khuraiya P et al, and Patel G et al 9,10 also some near similar rates above studies which are 1.26: 1 and 1.30:1 respectively. Some studies showed very high incidence in males compared to females like Kalavati GP et al, showed a very high male incidence which is more than three times that of the female which is 3.38:1.…”
Section: Discussionsupporting
confidence: 67%
“…In studies like Yadav RK et al, and Surve KM et al, had similar rates of male: female ratio which is 1.32:1 in both. 7,8 In other studies like Khuraiya P et al, and Patel G et al 9,10 also some near similar rates above studies which are 1.26: 1 and 1.30:1 respectively. Some studies showed very high incidence in males compared to females like Kalavati GP et al, showed a very high male incidence which is more than three times that of the female which is 3.38:1.…”
Section: Discussionsupporting
confidence: 67%
“…Some studies like Surve KM et al which had 79% and Yadav RK et al, study had 80% of anemia incidence in their studies both of which are similar to our present study. 9,10 But in other studies had very low incidence of malaria compared to this study. In Vaidya MS et al, study it was about 27.3%.…”
Section: Discussioncontrasting
confidence: 51%
“…The cases of P. vivax included 45 men and 15 females, while the cases of P. falciparum were 18 males and 22 females. The investigations conducted by Yadav RK et al [17] and Surve KM et al [18] reported a male to female ratio of 1.32:1, indicating comparable rates. Fever was the predominant manifestation in all 100 individuals, regardless of whether they were infected with falciparum or vivax.…”
Section: Discussionmentioning
confidence: 78%